2021
DOI: 10.3897/zookeys.1049.66063
|View full text |Cite
|
Sign up to set email alerts
|

Psychodidae (Diptera) of Azerbaijan and Georgia – faunistics with biodiversity notes

Abstract: Records of 46 Psychodidae (Sycoracinae 1, Trichomyiinae 1, Psychodinae 44) species/subspecies are presented in this paper based on specimens collected by sweep-netting in Azerbaijan and Georgia in 2019. Nine species are recorded for the first time since their original description; 12 species are new for Transcaucasia; 22 species are new for Azerbaijan; and 17 species are new for Georgia. Saraiella ressli montana Ježek, 1990 is proposed as a synonym of S. ressli Wagner, 1983, syn. nov. Knowledge of some aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Therefore, adequate attention must be paid to insects and other invertebrates, because they serve important ecosystem services and their loss may affect the whole functioning of the ecosystem. The less disturbed and close to natural habitats and localities deserve great attention, especially in protected areas (e.g., the Batsara Nature Reserve) and their vicinity (e.g., Kazbegi National Park), where we find not only a high species diversity of the family Psychodidae but also new species for science, as presented in Ježek et al (2021aJežek et al ( , 2021b and in this paper. The relatively large number of species new to science described on the basis of our recent sampling campaigns (e.g., Oboňa et al 2017;Ježek et al 2018Ježek et al , 2021aJežek et al , 2021b, together with the high degree of endemism, point to the importance of research on the Psychodidae family in the Caucasus.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Therefore, adequate attention must be paid to insects and other invertebrates, because they serve important ecosystem services and their loss may affect the whole functioning of the ecosystem. The less disturbed and close to natural habitats and localities deserve great attention, especially in protected areas (e.g., the Batsara Nature Reserve) and their vicinity (e.g., Kazbegi National Park), where we find not only a high species diversity of the family Psychodidae but also new species for science, as presented in Ježek et al (2021aJežek et al ( , 2021b and in this paper. The relatively large number of species new to science described on the basis of our recent sampling campaigns (e.g., Oboňa et al 2017;Ježek et al 2018Ježek et al , 2021aJežek et al , 2021b, together with the high degree of endemism, point to the importance of research on the Psychodidae family in the Caucasus.…”
Section: Discussionsupporting
confidence: 52%
“…Paradoxically, there are particularly large geographical gaps in biodiversity information in the Caucasus countries (Wetzel et al 2018), and the dipterans of this region are exemplary in this respect (Oboňa et al 2019). Much more attention should be devoted especially to preserved areas in nature reserves (NR), as evidenced, for example, by the high number of species found at a single locality in the Batsara Nature Reserve (Ježek et al 2021b). Another new species from this NR is described in this work.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Chaudhary and Aslam (2005) , Javaid et al (2006) ). The primary objective of faunistic studies are to document and record medical and economic important species of insects ( Ježek et al 2021 , Shehzad et al 2017 ). These studies are crucial for assessing the abundance of species found within a specific geographical area and monitoring the long-term shifts in population trends and diversity ( Ejsmont-Karabin 2019 , Shamna et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%